Research of the problems of international companies in the field of HR management - Kocziszky, György; Masalab, O. V. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The report identifies that successful HR management in global companies requires a comprehensive approach that includes strategic planning, the use of technology, and cultural sensitivity. These measures will allow companies to remain competitive in the face of globalization and a dynamically developing labor market.
Дослідження проблем міжнародних компаній у сфері управління персоналом
Keywords: personnel management; integrated approach; international companies; world experience; economics